2002
DOI: 10.1172/jci14596
|View full text |Cite
|
Sign up to set email alerts
|

Defective fatty acid uptake modulates insulin responsiveness and metabolic responses to diet in CD36-null mice

Abstract: IntroductionHigh blood fatty acids (FAs) are a common feature of insulin-resistant states (1), and raising the level of plasma FAs can induce acute insulin resistance (2). Plasma FAs and insulin sensitivity are negatively correlated (2), and an even stronger negative correlation can be documented with intramuscular triglycerides (TGs) (3,4). Randle et al. (5) originally stated that excessive muscle FA oxidation induced insulin resistance by inhibiting glucose oxidation. The mechanism proposed (6) involved ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 68 publications
(92 reference statements)
2
24
0
Order By: Relevance
“…However, we did observe that ApoE −/− Nrf2 −/− mice have significantly elevated triglyceride levels. This is consistent with previous studies demonstrating that CD36 -deficient mice have elevated plasma triglyceride levels [34] , [35] , further supporting the role of CD36 in ApoE −/− Nrf2 −/− mice. Mechanisms of the concomitant increase in blood glucose in Nrf2 deficient mice are less clear, although it may be attributed to dyslipidemia-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…However, we did observe that ApoE −/− Nrf2 −/− mice have significantly elevated triglyceride levels. This is consistent with previous studies demonstrating that CD36 -deficient mice have elevated plasma triglyceride levels [34] , [35] , further supporting the role of CD36 in ApoE −/− Nrf2 −/− mice. Mechanisms of the concomitant increase in blood glucose in Nrf2 deficient mice are less clear, although it may be attributed to dyslipidemia-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…This likely indicates an increased reliance on glucose oxidation, i.e., pyruvate conversion to acetyl-CoA. Although gene expression of the glucose transporters GLUT1 and GLUT4 was variable, it has been previously demonstrated that Ppara −/− mice ( 47 ), Cd36 −/− mice ( 48 ), and hLpL0 mice ( 23 ) all have increased cardiac glucose uptake. P407-treated fasting mice, which did not accumulate TGs in cardiomyocytes, tended to have increased glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of evidence suggests that a lowered Cd36 expression is metabolically protective while overexpression is likely to result in metabolic complications [ 47 , 48 ]. However, evidence also exists suggesting that Cd36 may be integral in glucose metabolism and insulin control [ 49 - 51 ].…”
Section: Discussionmentioning
confidence: 99%